Self-rated health and wellbeing among school-aged children with and without special educational needs: Differences between mainstream and special schools. (October 2018) - Rathmann, Katharina; Vockert, Theres; Bilz, Ludwig; Gebhardt, Markus; Hurrelmann, Klaus
Abstract: Background: Studies among students with special educational needs (SEN) in separate special schools (SSS) and mainstream schools (MS) are particularly applicable to educational attainment and social participation. However, indicators of health and wellbeing have rarely been considered. Aims: This study investigates two related topics: first, health and wellbeing differences between students with SEN in special schools (SSS) and students without SEN in regular schools, and second, the rarely considered question whether health and wellbeing among students with SEN differ between school settings (i.e. MS vs. SSS). Methods and procedures: Bivariate and multilevel analyses are applied with data from the German National Educational Panel Study (NEPS) with 5267 students (grade 7). Outcomes and results: After having controlled for background characteristics, students in SSS report higher likelihoods of poor self-rated health compared to students in higher track schools. Self-rated health of students with SEN does not significantly differ between MS vs. SSS. For life satisfaction, students with SEN show higher likelihoods of low life satisfaction when attending MS. Conclusions and implications: Teachers in inclusive settings are encouraged to establish class work and teaching that support a real change from class placement to inclusive culture in order to suitably support students with SEN.